Hardness and biocorrosion behaviour of a biodegradable Mg-3.0Zn-0.4Ca alloy after different processing routes - M.Á. Hernández; S. Fajardo; B. Torres; J. Rams; P. Hidalgo-Manrique (Materials & Design, 2025)
Biodegradable Mg alloys emerge as promising alternatives for biomedical applications, which requires a suitable combination of properties. In this work, a cast biocompatible Mg-3 wt% Zn-0.4 wt% Ca alloy, showing dendrites with large (α-Mg + Ca2Mg6Zn3) particles at the boundaries, was homogenised at 400 °C for 24 h. Afterwards, the alloy was subjected to either rolling or heat treatment or rolling followed by heat treatment. Microstructural characterisation revealed that (1) homogenisation causes the partial dissolution of particles, (2) rolling leads to deformed dendrites with basal orientation and (3) heat treatment results in a fully recrystallised microstructure with a grain size dependent on whether the alloy was previously rolled or not and promotes both the redistribution of the particles at the grain boundaries into a more connected configuration and the formation of a fine distribution of Ca2Mg6Zn3-rich particles within the grains. Hardness and corrosion tests in Hanks’ solution revealed that compared with the as-cast alloy homogenisation leads to higher corrosion resistance but slightly lower hardness, rolling to much higher hardness but the same corrosion rate and heat treatment to higher hardness and lower corrosion rate. The mechanical and biocorrosion behaviour was mainly ascribed to particle distribution and dislocation density, grain size and texture showing a negligible effect.